Rapid Spectral Dynamics in Hippocampal Oscillons - Zobaer, M. S.; Domenico, Carli M.; Perotti, Luca; Ji, Daoyun; Dabaghian, Yuri (Frontiers in Computational Neuroscience, 2022)
Neurons in the brain are submerged into oscillating extracellular potential produced by synchronized synaptic currents. The dynamics of these oscillations is one of the principal characteristics of neurophysiological activity, broadly studied in basic neuroscience and used in applications. However, our interpretation of the brain waves' structure and hence our understanding of their functions depend on the mathematical and computational approaches used for data analysis. The oscillatory nature of the wave dynamics favors Fourier methods, which have dominated the field for several decades and currently constitute the only systematic approach to brain rhythms. In the following study, we outline an alternative framework for analyzing waves of local field potentials and discuss a set of new structures that it uncovers: a discrete set of frequency-modulated oscillatory processes---the brain wave oscillons and their transient spectral dynamics.